Investigation Into An Optimum Mix Proportion For Foamed Concrete With High Stability In Water - Chan, Kwok Kwang (Universiti Malaysia Sarawak (UNIMAS), 2009)
This project will present the applicability in using foamed concrete to design pedestrian walkway on peat soil. The floatability of foamed concrete was tested in water with loading. The result shown that foamed concrete float in water and still be able to sustain some loading.